A pilot study on the effects of olfactory stimulation with white musk aromatic oil on psychophysiological activity: a crossover study - Fadilla Zennifa; Taisuke Nakashima; Yanli Xu; Saki Koshio; Erika Tomimatsu; Akiko Isa; Katsuya Satake; Fumi Kishida; Kuniyoshi Shimizu (Scientific Reports)
Abstract Studies on the compounds of aromatic oils and their effects on psychophysiological changes in humans are often conducted separately. To obtain better validation, a suitable protocol is needed that can be extrapolated to large-scale olfactory stimulation experiments. Unfortunately, this type of study is still rarely performed. In this situation, we propose a randomized crossover pilot study on olfactory stimulation with aromatic oils in relation to changes in psychophysiological activity by focusing on white musk aromatic oil due to its popularity in the community. Chemical profiling by TDU-GC-MS (thermal desorption gas chromatography/mass spectrometry) was performed to understand the compounds of the aromatic oils presented. To understand the changes in the participants’ impressions and mood states, POMS 2 (Profile of Mood States 2nd Edition) and VAS (Visual analogue scale) were performed in addition to physiological evaluation by using EEG (electroencephalogram), ECG (electrocardiogram) and salivary amylase measurements. The proposed pilot study showed “gorgeous”, “sweet”, and “like” impression toward white musk aromatic oil under VAS evaluation. Mood evaluation under POMS 2 variables such as Fatigue-Inertia (FI), Tension-anxiety (TA) and TMD (total mood disturbance) were significantly decreased under white musk aromatic oil inhalation. Under current protocol, we can also see the changes in autonomic activity and brain activity during olfactory stimulation. This pilot study could be the first step towards a larger sample size experiment on olfactory stimulation. This experiment has been registered to UMIN Clinical Trials Registry with register ID : UMIN000051972 on 24/08/2023.